P843 Post-vaccination kinetics of antibodies against hepatitis B surface antigen in inflammatory bowel disease patients: a single-centre cohort study. (25th January 2019) - Dimas, I; Voudoukis, E; Paspatis, G; Karmiris, K
Abstract: Background: Inflammatory bowel disease (IBD) patients are susceptible to post-vaccination immunity loss long-term. No data exist regarding the kinetics of antibodies against hepatitis B surface antigen (anti-HBs) after baseline vaccination. Our aim was to investigate changes in serial anti-HBs IgG measurements in immunised IBD patients. Methods: Consecutive IBD patients vaccinated and immunised against HBV either before or after diagnosis underwent measurement of anti-HBs IgG every 18–24 months during scheduled follow-up (FU) visits. Those with a negative ( < 10 mIU/ml) anti-HBs IgG titer received a booster dose (Engerix, GlaxoSmithKline®, Brentford, UK, 20 UG/ml). Immune response was defined as a positive (>10 mIU/ml for those not receiving and >100 mIU/ml for those receiving immunosuppressants [IMS]) anti-HBV IgG titer measured at least 3 months after the booster dose. Results: 349 IBD patients (females: 41%, Crohn's disease [CD]: 52.1%, median [IQR] age at diagnosis: 41.0 [27.1–56.0] and age: 48.8 [31.5–62.6] and disease duration: 2.0 [0.3–8.2] years at study entry) were prospectively screened and vaccinated if needed from January 2010 up to September 2018. In total, 151/349 patients (43.3%, females:43%, CD: 58.9%) have been followed up so far according to the protocol mentioned earlier. Thirty-two patients (21.2%, females: 34.3%, CD: 53.1%) lost immunity against HBV during FU, of those 17/32 (53.1%) while receiving IMS. So far, 18/32 patients have received a booster dose and 11/18 (61.1%) responded (7/11 [63.6%] under IMS therapy). A mean (±SD) anti-HBs titer of 41(±21.3) IU/ml was measured in four out of seven non-responders treated with IMS, inadequate however as per protocol ( < 100 mIU/ml). Interestingly, 15/18 patients (83.3%, 11/15 under IMS therapy) developed higher anti-HBs IgG titer compared with the one measured after baseline vaccination. Loss of immunity and booster dose responsiveness were not associated with either disease characteristics or therapeutic regimens administered. Conclusions: More than one fifth of our IBD patients vaccinated against HBV lose immunity overtime. A single booster dose can resume immune response in about two thirds of them. Immunosuppressants do not seem to influence either loss or resumption of immunity. These results should be interpreted with caution since our cohort is still small and verification in other cohorts is also mandatory.